Assessment of Compliance with OHADA Uniform Accounting Act by Public Limited Companies - Fossung, Michael Forzeh (Accounting and Finance Research, 2016)
Francophone African countries have made a tremendous effort in harmonising domestic standards and reporting with the International Financial Reporting Standards (IFRS). Moving from two distinct OCAM streams to two OHADA streams (effective 1985) and now one OHADA Uniform Accounting Act embodying 17 member countries (effective 2001) is a milestone towards harmonisation of reporting practice both domestically and internationally. This empirical study examines whether the effort of harmonisation, especially after the 2001 standards has resulted in the successful convergence of firms' accounting practices by analysing public limited liability companies' compliance with the OHADA Uniform Accounting Act and if such compliance has improved over time. The study has been carried out using the 2008 and 2009 annual reports of three public limited companies in the OHADA zone that translate their financial statements into IFRS. The ranks of closeness and compliance index have been used to analyse data. Findings reveal a relatively high level of compliance with the accounting regulation by sampling limited liability companies. The results also give an indication of harmonisation in accounting practice of limited companies within member countries as they were found to be substantially consistent in compliance, especially in countries that have instituted the Statistics and Tax returns (or "DSF") as a reporting medium.